Energy storage integration towards achieving grid decarbonization: A bibliometric analysis and future directions - Reza M.S.; Mannan M.; Wali S.B.; Hannan M.A.; Jern K.P.; Rahman S.A.; Muttaqi K.M.; Mahlia T.M.I. (Elsevier Ltd, 2023)
Decarbonization; Integration; Bibliometrics analysis; Condition; Decarbonisation; Energy; Energy storage technologies; Field mapping; Further development; Grid integration; Research areas; Scopus database; Energy storage